Methodical guidelines for performing laboratory work on the discipline "Analytical control and standardization of biotechnology products" - Bielykh, Iryna; Zviahintseva, O. V. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The main goal of the methodological instructions for laboratory work is to consolidate the knowledge gained during the study of the theoretical course, to master general methods of control of food and pharmaceutical biotechnology products, and to study methods of control of food raw materials. When performing laboratory work, it is necessary to study chemical, physicochemical, physical, and organoleptic methods for determining the composition and quality of raw materials and marketable products, if required, to assess their quality. The methodological instructions for laboratory work describe works that familiarize students with the production of individual products with the simultaneous study of one of the processes. Due to the long duration of their implementation in the absence of the necessary equipment, some of these works can be transferred to production or given to students as individual tasks for the period of production practice. Also, during laboratory work, students are familiarized with the assessment of the quality of incoming raw materials and finished products, with regulatory and technical documentation. The methodological guidelines contain two sections: 1) Quality assessment of raw materials and finished products of industrial biotechnology; 2) Analytical control of pharmaceutical biotechnology products. The main goal of the methodological guidelines is to help students systematize theoretical material and acquire practical skills and abilities, learn to work in an operating enterprise, find bottlenecks, observing safety regulations.
Keywords: methodological guidelines; laboratory work; biotechnology; standardization of biotechnology products; bioengineering; food raw